Analysis of Process Parameters for Resistance Spot Welding on Galvanized Steel using Taguchi Method - N.F. Hayazi; P. Jaraman; D.S. Che Halin; F.M. Foudzi; M. Nabiałek; P. Vizureanu (Archives of Metallurgy and Materials)
Resistance spot welding (RSW) involved two or more sheets of metal that are welded together with or without filler materials. This paper discussed the optimization of RSW process parameters that were varied on galvanized steel below 6 kA by using Taguchi method. Galvanized steel can be more difficult to spot weld than any other uncoated metal due to the tendency of zinc coating alloying with electrodes. The three process parameters are welding current, welding time and holding time. The type of OA used in this study was L9. Subsequently, tensile and Vickers microhardness tests were conducted on the sample. Results from these tests were used to calculate the S/N ratio, ANOVA and confirmation test. The optimal parameters value and percentage of contributing factors to the welding can be identified. It will help to produce high-quality weld joints.